PERANCANGAN ROBOT PENGIKUT GARIS BERBASIS MICROCONTROLLER - Steff Turangan; Jotje Rantung; Markus K umboh (JURNAL POROS TEKNIK MESIN UNSRAT, 2016)
Â  Currently the development of robot technology is growing rapidly. The technology is utilized and developed to assist people in doing their activities more easily and efficiently. One application of the robotic technology is the line follower robot that is widely used in transportation in industrial field. The purpose of this thesis was to determine the working principle and reliability of the line follower robot with its main components that are power supply, sensors, microcontrollers, and motor drivers. The methodology of the research is to design and to assamble a line follower robot and perform direct testing of the reliability on the on 6,5m â€œÏ¨â€ - shaped tracked. The results show that the stages of the assembling of the line follower robot consist of the installation of each circuit and the installation of the drive system in robot frame. The test results show that the line follower robot is able to pass through the track well with average speed of 0,22 m/sec. Keywords : Design, Line Follower Robot, Microcontroller